The Borrelia burgdorferi CheY3 response regulator is essential for chemotaxis and completion of its natural infection cycle. (11th July 2016) - Novak, Elizabeth A.; Sekar, Padmapriya; Xu, Hui; Moon, Ki Hwan; Manne, Akarsh; Wooten, R. Mark; Motaleb, MD A.
Summary: Borrelia burgdorferi possesses a sophisticated and complex chemotaxis system, but how the organism utilizes this system in its natural enzootic life cycle is poorly understood. Of the three CheY chemotaxis response regulators in B . burgdorferi, we found that only deletion of cheY3 resulted in an altered motility and significantly reduced chemotaxis phenotype. Although Δ cheY3 maintained normal densities in unfed ticks, their numbers were significantly reduced in fed ticks compared with the parental or cheY3 ‐complemented spirochetes. Importantly, mice fed upon by the Δ cheY3 ‐infected ticks did not develop a persistent infection. Intravital confocal microscopy analyses discovered that the Δ cheY3 spirochetes were motile within skin, but appeared unable to reverse direction and perform the characteristic backward–forward motility displayed by the parental strain. Subsequently, the Δ cheY3 became 'trapped' in the skin matrix within days of inoculation, were cleared from the skin needle‐inoculation site within 96 h post‐injection and did not disseminate to distant tissues. Interestingly, although Δ cheY3 cells were cleared within 96 h post‐injection, this attenuated infection elicited significant levels of B . burgdorferi ‐specific IgM and IgG. Taken together, these data demonstrate that cheY3 ‐mediated chemotaxis is crucial for motility, dissemination and viability of the spirochete both within and between mice and ticks.